Credit analysis of financial institutions - Grier, Waymond A. (London : Euromoney, 2007)
This second edition builds on the success of the first edition - the first book to look at how credit analysis of each major type of financial institution is best approached in an environment of integration, consolidation and globalisation within the financial services industry.
Includes bibliographical references (p. 131-132).
oif 29/07/15 gau 02/08/16
Loan
Keywords: Financial institutions; Credit analysis; Banks and banking